Address-light and energy aware routing protocol for wireless sensor network - Hamdollah Ghamgin (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2019)
In recent years, sensor networks applications were used in many criteria. Because of its vast applications, so many researchers studied these networks. Wireless sensor networks contain significant number of sensor nodes; they are suitable medium for collecting and sending data or informing the sink about an event. This study presents a new integrated method for routing in sensor networks which is based on remaining energy of the nodes and existing space between each node and the sink. This method is more suitable for large and medium volume of data. Lifetime enhancement of the network is the main purpose of this method which is obtained by fair division of nodes roles in transmission of data to the sink. In ALERP algorithm (Address Light, Label-Based and Energy-Aware Routing Protocol), in order to reduce network overload and energy consuming as well as enhancement of network lifetime, we used predetermined routes as well as routing based on packet labels. Energy consumption in the entire network is another advantage of this method. The existence of various parameters on this algorithm will lead to more flexibility of it. Generally, conducted simulations indicate higher uniformity in energy consumption of nodes.